O ACORDO DE ESCAZÚ/2018 COMO INSTRUMENTO DE DEMOCRACIA AMBIENTAL E DIREITOS HUMANOS NO BRASIL - Domenico Treccani, Girolamo; Pinheiro, Olinda Magno (Veredas do Direito, 2022)
ABSTRACT: This article aims to analyze, from the perspective of the exercise of environmental democracy, the pressing importance of ratifying and enforcing the Escazú-2018 Agreement, especially for the Brazilian State. Therefore, theoretical considerations were outlined through bibliographical and documentary research that reaffirm the coherence of the dialogue among sources of domestic and international law, to defend environmental democracy and human rights. Using the deductive method, it is concluded the important contribution of this International Document, which in order to regulate the triad of access rights or environmental procedures, will consolidate the defense of environmental democracy and human rights related to the defense of the environment.